2005
DOI: 10.1016/s0753-3322(05)80012-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronoecological health watch of arterial stiffness and neuro-cardio-pulmonary function in elderly community at high altitude (3524 m), compared with Japanese town

Abstract: Effects of high altitude on arterial stiffness and neuro-cardio-pulmonary function were studied. Blood pressure (BP) and heart rate (HR) were measured in a sitting position on resting Ladakhis, living at an altitude of 3250-4647 m (Phey village, 3250 m: 17 men and 55 women; Chumathang village, 4193 m: 29 men and 47 women; Sumdo village, 4540 m: 38 men and 57 women; and Korzok village, 4647 m: 84 men and 70 women). The neuro-cardio-pulmonary function, including the Kohs block design test, the Up and Go, the Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Importantly, one study has suggested that CAVI levels are higher in residents living at high altitude than those at sea level, and increases in hematocrit and oxidative stress by hypoxia are speculated as the causes. 21 In fact, the increased hematocrit levels in Mongolian subjects have already been reported. 20 Therefore, the results of higher CAVI levels in the Mongolian subjects may be partly due to such hypoxia-related factors.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Importantly, one study has suggested that CAVI levels are higher in residents living at high altitude than those at sea level, and increases in hematocrit and oxidative stress by hypoxia are speculated as the causes. 21 In fact, the increased hematocrit levels in Mongolian subjects have already been reported. 20 Therefore, the results of higher CAVI levels in the Mongolian subjects may be partly due to such hypoxia-related factors.…”
Section: Discussionmentioning
confidence: 88%
“…As a possible mechanism, the residential altitude is very different between Japanese and Mongolian people and it has been documented that the altitude can contribute to circulatory characteristics such as HR and BP. 20,21 The mean altitude of JMU (Tochigi prefecture) is approximately 50 m (165 feet) and that of Ulaanbaatar is 1350 m (4429 feet) above sea level. In our study, the higher levels in HR and BP in the Mongolian subjects may be explained by the earlier study results that HR and BP (DBP in particular) increased with rising altitude levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this may be the existence of differences in environmental factors. The enhanced effect of high altitude on not only blood pressure 22) but CAVI 5,23) in Mongolia has been reported. The lowered effect of high altitude on plasma glucose has also been reported 24) , and in fact our studied Mongolian DM patients had lower glucose levels.…”
Section: Discussionmentioning
confidence: 96%
“…These behavioral risk factors may be also called primary risk factors of NCDs [11]. Apart from these social determinants of health, high altitude, geomagnetic activity, and sleep disruption are other environmental factors which can predispose circadian variability in biological functions resulting in NCDs [13][14][15][16]. In high income countries, many experts believe that poverty is the major cause of deaths and disability due to NCDs [1][2][3].…”
Section: Social Markers Of Lifestyle and Healthmentioning
confidence: 99%